Making technology investments profitable ROI road map from business case to value realization - Keen, Jack M. (Wiley, 2011)
"A guide to getting the crucial business case right-every time Showing professionals how to calculate the value of typical budgeting and funding requests quickly and easily, Making Technology Investments Profitable, Second Edition applies the "Value Realization" process, using proven strategies that maximize the business payoff from IT projects. Filled with case studies, this innovative book enables managers to confidently quantify, in a matter of minutes, the true business value of funding a desired project. New edition explains how to proactively manage the conversion of a business case's value promise to its value realization Includes dozens of new case studies on realizing maximum value from IT enabled investments from various industries and around the world Most of the popular checklists and tables from the current edition will be retained and numerous new ones will be added A dedicated Web site containing additional material, case studies, chat rooms, and blogs on the value-realization process Providing new insights on how to get the crucial business case right, while also explaining how to proactively manage the conversion of the business case's value promise into the value reality of a completed project, the Second Edition of Making Technology Investments Profitable unveils an unexpectedly straightforward solution to this disconcerting situation-a very pragmatic process of value realization involving role, responsibility, and mindset changes for senior executives, as well as project managers and technical staff."--